“Кёнгүг Тэжон Жүхэ” -д тэмдэглэсэн монгол хэлний бичгүүд: Чусоны үед хэвлэгдэп гарсан хууль цаазын бичгийн тайлбар - С.Батхишиг (Acta Mongolica, 2007)
The Mongolian language books, such as Mongò nogoltae (), Ch’obhae Mongo () and Mongo yuhae () published by Chuson’s "Sayogwôn" at the end of XVIII century are inherited to our days are known in the Mongolian studies as "The three books for the study of Mongolian ". The information on issuing of 16 books written in Mongolian in Korea earlier the abovementioned three books is kept in the source called “Chông gûg dae jôn” ( ) The source has a note on bibliography and proper name comments, which was a subject for a number of researches in Korean and English (it can be reviewed in the bibliography of the article). Among the Mongolian researches, B.Sumyabaatar has mentioned about it. In this article the 16 books are introduced briefly.